Analysis of the efficacy and safety of pregabalin in reducing the post-total knee arthroplasty sleep disturbances - Sanjay Bhalchandra Londhe; Ravi Teja Rudraraju; Ravi Vinod Shah; Govindkumar Baranwal; Anay Shah; Ishan Londhe; Dolly Singh (Journal of Orthopaedic Reports)
Background: Total knee arthroplasty (TKA) helps to relieve pain, improve the mobility and quality of life in patients with end stage knee arthritis. Various studies have reported sleep disturbances to be the common post-TKA complication. The purpose of the present study is to analyze the efficacy and safety of pregabalin in reducing post-TKA sleep disturbances. Methods: A prospective study was conducted at a single center, where we compared the sleep disturbances post-TKA between two groups. The inclusion criteria were patients undergoing unilateral TKA for end stage osteoarthritis. Patients with previous history of psychiatric/insomnia medication were excluded. Sample size was estimated to be 34 patients in each group for 10 % improvement of the sleep quality with alpha error of 0.05 and beta error of 0.1 with power of study being 90 %. The patients were randomized in two groups by random envelope method. Group 1 received oral paracetamol 1 g three times a day after food for 8 weeks. Group 2 received a night dose of extended release of 75 mg of pregabalin in addition to paracetamol. The sleep quality of the two groups was assessed with Pittsburgh Sleep Quality Index (PSQI) by an independent observer. The statistical significance was tested with comparison of means utilizing students t-test. P value < 0.05 was considered significant. Results: There was no statistically significant difference between the two groups as regards the age, gender, body mass index, degree of deformity and associated comorbidities. The mean PSQI for group 1 and 2 at 8 weeks post-TKA was 7.70 ± 0.83 and 6.25 ± 0.92 respectively (p value < 0.0001). There were no adverse side effects like giddiness, increased frequency of micturition in group 2. Conclusion: Use of extended release pregabalin (75 mg) at night-time post-TKA significantly reduces sleep disturbances and improves sleep quality.